Investigation of dielectric properties and diffraction efficiency enhancements caused by photothermal effect in DR9 dye-doped nematic liquid crystal - Koysal, Oguz; Okutan, Mustafa; Gokcen, Muharrem (ELSEVIER, 2011)
In this work, we studied dielectric properties and laser-induced refractive index changes originating from photothermal effects of liquid crystal material doped with Disperse Red 9 (DR9) dye. Dye concentration is arranged to be between percentages changing from 0.2 wt.% to 1 wt.% in E63 nematic liquid crystal. Nonlinear optical properties such as diffraction efficiency (eta) and refractive index modulation (Delta n) were investigated by diffraction grating measurements. It was found the diffraction efficiency of pure E63 nematic liquid crystal is 1%. As the doping amount of DR9 dye in nematic LC is increased, diffraction efficiency took higher values and the maximum diffraction efficiency of 10% was gained with E63 doped with 0.8 wt.%DR9 dye. Moreover. dielectric permittivity and dielectric anisotropy values of the samples were investigated in the frequency range of 100 Hz-10 MHz by using dielectric spectroscopy technique. It was observed that dielectric constant values of the liquid crystal material are strongly affected by doping with dye. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dye; Liquid crystal; Photothermal effect; Holography; Diffraction efficiency; Dielectric anisotropy; Optics